Contractors Perceptions of Effects of Project Overhead Costs on Building Project Performance in South-South of Nigeria - Ujene, A.O.; Idoro, G.I.; Odesola, I.A. (Institute of Research and Community Outreach - Petra Christian University, 2013)
This study assesses 12 types of project overhead costs, 6 methods of allocation and 15 factors which affect project overhead costs in South-South of Nigeria. The objective is to compare small and medium contractors’ perception of the methods of allocation, factors affecting project overhead costs and the effect of the types of project overhead costs on cost, time and quality of the projects. Data were obtained through 501 structured questionnaires administered to small and medium contractors and analysed using mean item score, and Mann-Whitney U test. The results reveal that contractors perceive that supervision costs, cost of rework, equipment management costs, general field expenses, and temporary works costs were prominent overheads affecting cost, time, and quality performance of projects. There is no difference in the contractors’ perceptions of issues affecting overhead costs. It is recommended that contractors should give adequate priority to significant project overheads and their influencing factors.